Super Yachts : cruising with power and style - Kramer, Sibylle, 1967- ([Berlin] : Braun, 2012)
Motor yachts are the essence of luxury, comfort and boundless freedom. Their design and fittings stand for premium quality. As swimming mansions they are exposed to very particular conditions that confront the boat designer with special challenges. The materials must be able to withstand the forces of wind and weather, and spatial concepts must adapt to the special physical characteristics of water. The selection of approximately 40 motor yachts, each presented on two to three double pages, covers the entire spectrum of this species of boat: from relatively affordable, serially produced motor yachts, to the 150 meter long, one-of-a-kind luxury mega yacht. The volume is an invitation to discover and explore the maritime visions of the 21st century.
Includes designers' index.
Keywords: Yacht designer; Yachts and yachting -- Design and construction